1986
DOI: 10.1002/bem.2250070403
|View full text |Cite
|
Sign up to set email alerts
|

Microwave effects on isolated chick embryo hearts

Abstract: This study was designed to examine the effects of microwaves on the electric activity of hearts as a means of elucidating interactive mechanisms of nonionizing radiation with cardiac tissue. Experiments were performed on isolated hearts of 9-12-day-old chick embryos placed in small petri dishes. Oxygenated isotonic Ringer's solution at 37 degrees C permitted heart survival. Samples were irradiated at 2.45 GHz with a power density of 3 mW/cm2. The heart signal was detected with a glass micropipet inserted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Yee et al [27,28] demonstrated in a series of experiments that bradycardia could be caused by electrode artifacts and by thermal influences; at constant temperatures, no bradycardia or tachycardia was found. Caddemi et al [29] reported different effects depending on modulation characteristics; continuous wave radiation of isolated chicken embryo hearts caused a slight bradycardia, whereas pulse-modulated fields led to an increase of heart rate and locking of cardiac rhythm to the modulation frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Yee et al [27,28] demonstrated in a series of experiments that bradycardia could be caused by electrode artifacts and by thermal influences; at constant temperatures, no bradycardia or tachycardia was found. Caddemi et al [29] reported different effects depending on modulation characteristics; continuous wave radiation of isolated chicken embryo hearts caused a slight bradycardia, whereas pulse-modulated fields led to an increase of heart rate and locking of cardiac rhythm to the modulation frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of some microwave effects at the cell membrane level led us to investigate the interactions betwen EM fields and cellular systems, both by experimental methods and theoretical analysis [Bernardi and D'Inzeo, 1984;Bernardi et al, 1985;Caddemi, 1986;Caddemi et al, 19861. Some recent studies on the interactions between EM fields and living cells suggest that the field may directly affect the function of the transmembrane protein channels [Adey, 1984;Arber and Lin, 1985;Chiabrera et al, 1984;McLeod and Liboff, 19861.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have not reported altered calcium physiology in neurons or cardiac tissue due to EMF [Schwartz and Mealing, 1993;Wolke et al, 1996;Green et al, 2005]. Some studies have focused on the direct effects on electrophysiological properties during the course of exposure [Caddemi et al, 1986]. In our studies, the beat rate of the spheroids was recorded during exposure.…”
Section: Discussionmentioning
confidence: 97%
“…The heartbeat of exposed chick embryonic hearts locked to the modulation frequency of pulsed microwaves [Caddemi et al, 1986], and an irregular heartbeat was altered to a regular one by an appropriate pulse repetition [Tamburello et al, 1993]. Some pioneering work was done by Seaman and DeHaan [1993] with cardiac-cell aggregates, which revealed altered interbeat intervals during exposure to 2.45 GHz microwaves.…”
Section: Discussionmentioning
confidence: 98%